Bilateral optic neuropathy as a complication of allogeneic hematopoietic stem cell transplantation - Lestak, Jan; Mlcak, Petr; Kuba, Adam; Maresova, Klara; Kyncl, Martin; Tintera, Jaroslav; Fus, Martin (Biomedical papers, 2023)
Background. The authors present a case study which describes the development of bilateral optic neuropathy as a complication of allogeneic hematopoietic stem cell transplantation (HSCT) in a patient who underwent a transplant for B-cell acute lymphoblastic leukemia (B-ALL). The patient, who was in remission with regard to the underlying hematological disease, developed edema of both optic discs and maculas three months after transplantation. The morphological finding regressed after treatment with corticoids and comprehensive systemic anti-infective therapy. However, the loss of function was not entirely restored. Case Report. One year after the healing, the atrophy of the optic discs persisted, with corresponding findings in vessel density (VD), retinal nerve fibre layer (RNFL) and visual field changes. Electrophysiological examination by pattern electroretinogram (PERG) showed an alteration in retinal ganglion cells in the left eye, but with significant damage to nerve fibres on both sides. Visual evoked potential (VEP) verified bilateral non-inflammatory neurogenic lesions. This finding was also confirmed by functional magnetic resonance imaging (fMRI). Examination by structural magnetic resonance imaging (MRI) showed inflammatory changes in the optic nerve sheaths over time and a consequent marked narrowing of them. Conclusion. The authors believe that edema of the optic discs and maculas was caused by a combination of several factors. Firstly, MRI showed inflammatory changes in the optic nerve sheaths, which led to a blockade of axoplasmic transport. Another factor that may have played a part in the outcome was endothelial damage to blood vessels with impaired microcirculation supplying the optic nerve fibres, which contributed to the occurrence of macular edema.
Keywords: optic disc; macula; edema; lymphoblastic leukemia; hematopoietic stem cell; allogeneic transplantation; MRI